Preparation of laccase mimicking nanozymes and their catalytic oxidation of phenolic pollutants - Xu, Xiaojian; Wang, Jinghui; Huang, Renliang; Qi, Wei; Su, Rongxin; He, Zhimin (Catalysis science & technology, 2021)
The construction of a nanozyme that mimics a natural enzyme is a promising strategy to obtain a highly stable catalyst. Laccases are members of copper-containing oxidases, as environmental catalysts, and show significant potential in biotechnology and environmental remediation. In this study, inspired by the active site and electron transfer of laccase, a new laccase mimic (defined as CA-Cu) was synthesized via the coordination of copper with a cysteine (Cys)-aspartic acid (Asp) dipeptide. The as-prepared CA-Cu nanozyme exhibits significant laccase-like activity and catalytic oxidation of a wide range of phenolic pollutants, such as 2,4-dichlorophenol, phenol, p -chlorophenol, 2,6-dimethoxyphenol, hydroquinone, o -nitrophenol and o -aminophenol hydroquinone. It has a similar K m (Michaelis constant), a higher v max (maximum rate) and better recyclability than laccase at the same mass concentration. In addition, the CA-Cu nanozyme is robust in a broad temperature range (0-100 °C), at extreme pH and under long-term storage. Surprisingly, the catalytic performance of the CA-Cu nanozyme was enhanced under high-salt conditions or at high concentrations of heavy metal ions, which lead to severe loss in the catalytic activity of laccase. We believe that this nanozyme is a promising environmental catalyst for the treatment of phenolic pollutants under high-salt or heavy metal ion conditions. The construction of a nanozyme that mimics a natural enzyme is a promising strategy to obtain a highly stable catalyst.